Liver Transplantation Outcome in Patients With Angiographically Proven Coronary Artery Disease: A Multi‐Institutional Study. Issue 1 (5th November 2012) - Wray, C.; Scovotti, J. C.; Tobis, J.; Niemann, C. U.; Planinsic, R.; Walia, A.; Findlay, J.; Wagener, G.; Cywinski, J. B.; Markovic, D.; Hughes, C.; Humar, A.; et al.
<x xml:space="preserve">Abstract</x> Over the last decade the age of liver transplant (LT) recipients and the likelihood of coronary artery disease (CAD) in this population have increased. There are no multicenter studies that have examined the impact of CAD on LT outcomes. In this historical cohort study, we identified adult LT recipients who underwent angiography prior to transplantation at seven institutions over a 12‐year period. For each patient we recorded demographic data, recipient and donor risk factors, duration of follow‐up, the presence of angiographically proven obstructive CAD (≥50% stenosis) and post‐LT survival. Obstructive CAD was present in 151 of 630 patients, the CAD(+) group. Nonobstructive CAD was found in 479 patients, the CAD(−) group. Patient survival was similar for the CAD(+) group (adjusted HR 1.13, CI = [0.79, 1.62], p = 0.493) compared to the CAD(−) group. The CAD(+) patients were further stratified into severe (CADsev, >70% stenosis, n = 96), and moderate CAD (CADmod, 50–70% stenosis, n = 55) groups. Survival for the CADsev (adjusted HR = 1.26, CI = [0.83, 1.91], p = 0.277) and CADmod (adjusted HR = 0.93, CI = [0.52, 1.66], p = 0.797) groups were similar to the CAD(−) group. We conclude that when current CAD treatment strategies are employed prior to transplant, post‐LT survival is not significantly different between patients with and without obstructive CAD.